THE ROLE OF PROFITABILITY IN MEDIATING THE EFFECT OF CAPITAL STRUCTURE AND FIRM GROWTH ON THE FIRM VALUE OF TRANSPORTATION AND LOGISTICS COMPANIES SECTOR - Silvia, Jacklyn Dona; Wuryani, Eni (LPPM Universitas Bina Bangsa, 2024)
This study aims to examine whether there is an influence of capital structure and firm growth on firm value and whether profitability can be an intermediary or mediation on the influence between these variables. The population in this study were transportation and logistics companies listed on the Indonesia Stock Exchange totaling 37 companies, and 17 of them met the purposive sampling criteria to be used as research samples. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with SPSS version 25 and the sobel test. The results of this study provide evidence that the variables of capital structure and firm growth have a significant positive effect on profitability, capital structure has a significant negative effect on firm value, firm growth has no effect on firm value, and profitability has a significant positive effect on firm value. And profitability is not able to mediate the effect of capital structure and firm growth on firm value